Studies on the Proximate Composition, Quality and Heavy Metal Concentration of Sun-dried Bombay Duck and Sun-dried Ribbon Fish of Cox’s Bazar District of Bangladesh - Jamil, MGM; Hossain, MN; Mia, MM; Mansur, MA; Uga, S (Journal of Environmental Science and Natural Resources, 2017)
Proximate composition, quality aspect and heavy metal concentration of sun-dried Bombay Duck (Harpodon nehereus) and sun-dried Ribbon fish (Trichiurus haumela) were studied in a series of laboratory experiments. Sun-dried fishes were collected from a fish market of Cox‟s Bazar town. These sun-dried marine fishes were collected from the stock after first drying procedure. Organoleptically most of these sun-dried fishes were in „B‟ grade that means in „Good‟ condition (SDP 2.33 and 2.35 respectively). Crude Protein, Lipid, Moisture, Ash, TVB-N and TMA-N content (%) of sun-dried Bombay Duck (Harpodon nehereus) was 32.21±1.05 %, 3.51±0.38 %, 37.26±0.70 %, 16.22±0.56 %, 115.45±1.73 mg/100g, 9.37±0.13 mg/100g respectively. Whereas in sun-dried Ribbon fish (Trichiurus haumela) the content (%) of Crude Protein, Lipid, Moisture, Ash, TVB-N and TMA-N was 31.64±1.28 %, 5.06±0.10 %, 35.78±0.97 %, 12.33±0.27 %, 107.69±1.37 mg/100g and 9.91±0.23 mg/100g respectively. Heavy metal concentration i.e. Cd, Cr, Pb, Cu and Zn concentration (ppm) in sun-dried Bombay Duck (Harpodon nehereus) was 0.82, 8.38, 8.28, 2.21, 55.38 ppm. Whereas heavy metal concentration (ppm) in sun-dried Ribbon fish (Trichiurus haumela) was Cd 0.48 ppm, Cr 6.96 ppm, Pb 5.46 ppm, Cu 1.40 ppm, Zn 19.95 ppm. J. Environ. Sci. & Natural Resources, 10(1): 55-60 2017